Ultrasound-Assisted Esterification of Valeric Acid to Alkyl Valerates Promoted by Biosilicified Lipases - Cebrián-García, Soledad; Balu, Alina M.; Luque, Rafael (Frontiers in Chemistry, 2018)
A novel, environmentally friendly and sustainable ultrasound-assisted methodology in the valorisation of valeric acid to alkyl valerate using a biosilicified Lipase from Candida Antarctica (LCA) is reported. This one-pot room temperature methodology of enzyme biosilicification leads to biosilicified lipases (Bio-LCA) with improved activity and reaction efficiency as compared to free enzymes. Yields in the ultrasound-promoted esterification of valeric acid was ca. 90% in two hours with 15% m/v of Bio-LCA (616 U/ mg biocatalyst enzymatic activity) and a molar ratio 1:2 (valeric acid: ethanol), slightly superior to that observed by the free enzyme (75% conversion, 583U/mg biocatalyst enzymatic activity). The reuse of enzymes in these conditions was tested and the results show a relatively good reusability of these biosilicified enzymes under the investigated conditions, particularly preserving fairly stable specific activities (616 vs 430 U/mg biocatalyst after four reuses).